EFFECTIVENESS OF ADAPTED ENGKLEK GAME FOR IMPROVING STUDENT’S KALAM IKHBARI SKILLS - Putri, Annida Khoirunnisa; Mahyudin, Erta; Edidarmo, Toto (Yayasan Amanah Nur Aman, 2025)
Arabic speaking skills are among the essential abilities that second-language learners must master. However, most students find it difficult to speak Arabic due to limited vocabulary and lack of speaking practice in class. Therefore, this study aims to determine the effectiveness of the modified Engklek game as a learning medium in improving students’ kalam ikhbari skills in Arabic learning. This study employs a quantitative approach using a quasi-experimental method. The research subjects were students from Classes VIII A and VIII B at Al-Fatih 1 Islamic Integrated Junior High School, each consisting of 32 students. Data were collected through oral tests using a pretest and posttest model. The game modification for speaking skills was carried out by incorporating Arabic learning elements into the game system, such as thematic vocabulary and sentence structure patterns. Furthermore, students’ roles were designed to be not only active participants but also direct language users in communicative and enjoyable situations. The results showed a significant improvement in the experimental group’s speaking ability, with an average pretest score of 33 and a posttest score of 65, while the control group experienced only a slight increase from 35 to 40. The improvement in the experimental group’s speaking skills fell into the moderate category, with a percentage increase of 47%. Thus, the use of the modified Engklek game proved effective in enhancing students’ speaking skills in Arabic learning.